Special education from an inclusive perspective: advances, problems and challenges for managers and teachers of basic education schools in Angola - EDUARDO SALA (RCMOS – Revista Científica Multidisciplinar O Saber, 2025)
Angola is a country located in the South-Central region of Africa, which after independence in 1975, experienced 27 long years of civil war that ended in 2002, a dark page in the country's history that left thousands of people mutilated, including children who were victims of anti-personnel mines. This group includes children and adolescents with various disabilities, ranging from motor to intellectual. Using a qualitative approach and a systematic bibliographic research method, this article analyzes the situation of Special Education from an Inclusive Perspective in Angola, as well as the status of the institutionalization of national laws and international treaties on the rights of people with disabilities in the country. The results of this research indicate that, although the country has made progress from a legislative/regulatory point of view, the institutionalization of the rights to education of people with disabilities falls short of expectations. Structural, institutional and social barriers continue to be imposed on this group of national citizens, hindering the possibility of academic-professional and, therefore, social advancement of thousands of children in the country.